Optimal Interactive Rainfall Maps (Iraq) in Client Side and Google Earth - Ali, Hussain Zaydan; Al-Qaraawi, Salih M.; Arab, Ghusoon Eiden (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Global environment change has become a worldwide concern in recent years. Rainfall is an important climatologically parameter, and knowledge of its temporal and spatial patterns is useful for researchers working in many disciplines, such as optimal management of agriculture, environment and related activities. Meteorological data coming from stations are the most reliable and used sources to assess the climate condition of an area. Historical records of monthly rainfall data for the time period 2003-2013 were acquired from the Iraqi Meteorological Organization and Seismology (IMOS). The long-term data were collected from 24 weather stations. To obtain optimal maps of rainfall we also used the Tropical Rainfall Measuring Mission (TRMM). In this paper we tried to explain the possibility of vector format KML and its properties for thematic mapping in Google Earth closer, which is used to display the resulting map outputs. Maps alone are compiled by the client using the Web site browser for transferring input variables to the server, where they are processed and map data is subsequently generated according to client requirements.